A new Danish inventory for IFR flights used to improve national fuel use and emission estimates - Winther, Morten (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
This paper describes 1) a new model developed for calculating the fuel use and emissions for all IFR (Instrumental Flight Rules) jet and turbo-prop flights in Denmark, Greenland and the Faroe Islands in 1998 and 2) recommendations to improve the current model used for national estimates based on the new model results. The new model uses the new detailed CORINAIR (COoRdination of Information on AIR emissions) calculation principle. It was feasible to set up the inventory system. Air traffic data was provided by EUROCONTROL and information on aircraft types and airport codes was obtained from ICAO (International Civil Aviation Organization). All aircraft were grouped into 24 representative aircraft types for which fuel use and emission data were available in the CORINAIR databank per LTO and for distance classes. Cruise results were estimated for each flight by adjusting for the given flight length. Except for international Landings and Take Offs (LTO< 3000ft) in Copenhagen Airport it is recommended to update all fuel use and emission data in the current model for national estimates. The improved data can be derived from the new model results. There is also a need to further scrutinize for which purposes the aviation fuel is used in Danish Airports. The present study’s results could be valuable in a cross-check examination of statistical data versus model estimates.